ANALISIS KESANTUNAN BERBAHASA PADA MEDIA INSTAGRAM (KAJIAN PRAGMATIK) - Rizal Sukandi; Irwan Siagian; Nadya Maharani (FKIP, Universitas Palangka Raya, 2022)
The this study examines language politeness on social media pragmatic study instagram. The purpose of this study was to find out the politeness of public comments on Erick Thorhir's posts on Instagram social media. The method used in this research is a qualitative descriptive method. The data source in this research is secondary data from social media Instagram in the form of public comments on Erick Thohir's posts. The instrument in this study was an analysis table of documentation data. The data analysis technique collects data from public comments on Erick Thorhir's posts, analyzes and describes the data using theories obtained from studying books and other scientific works, analyzes politeness, explains politeness analysis according to the rules of maxims and draws conclusions. The results of this study show the reality of language politeness, namely in the speech of public comments on Eric Thohir's posts on Instagram social media, using six principles of politeness so that it can be concluded that the analysis of each data shows that the speech is polite.